Hepatorenal Syndrome: Outcome of Response to Therapy and Predictors of Survival - Jan Heidemann; Christoph Bartels; Christoph Berssenbrügge; Hartmut Schmidt; Tobias Meister (Gastroenterology Research and Practice)
Aim. Treatment of hepatorenal syndrome (HRS) in patients with liver cirrhosis is still challenging and characterized by a very high mortality. This study aimed to delineate treatment patterns and clinical outcomes of patients with HRS intravenously treated with terlipressin. Methods. In this retrospective single-center cohort study, 119 patients (median [IQR]; 56.50 [50.75–63.00] years of age) with HRS were included. All patients were treated with terlipressin and human albumin intravenously. Those with response to treatment (n=65) were compared to the patient cohort without improvement (n=54). Patient characteristics and clinical parameters (Child stage, ascites, hepatic encephalopathy, HRS type I/II, and initial MELD score) were retrieved. Univariate analysis of factors influencing the success of terlipressin therapy and Cox regression analysis of factors influencing survival was carried out. Results. One-month survival was significantly longer in the group of responders (p=0.048). Cox regression analysis identified age [Hazard ratio, 95% confidence interval (CI); 1.05, 1.01–1.09, resp.], alcohol abuse [HR 3.05, 95% CI 1.11–8.38], duration of treatment [HR 0.92, 95% CI 0.88–0.96], and MELD score [HR 1.08, 95% CI 1.02–1.14] to be independent predictors of survival. Conclusions. Survival of HRS patients after treatment depends on age, etiology of liver disease, and the duration of treatment.